Implementasi Algoritma Vigenere Cipher Untuk Keamanan Data Bantuan Sosial Di Desa - Pazri Pazri; Abdul Halim Hasugian (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Data security in the digital era is very important. Village governments often manage sensitive data related to social assistance, such as recipient names, ID numbers, types of assistance, and other details. This data is very vulnerable to leaks or misuse, especially if there is no strong security system in place. This highlights the importance of implementing technology that supports data security. By implementing cryptographic algorithms such as the Vigenere Cipher, the village government can protect its community's data from potential threats. This algorithm uses a flexible secret key, making it ideal for securing small to medium-scale data, such as social assistance data. The Vigenere Cipher algorithm is applied to secure social assistance data in Lawe Sempilang Village, such as recipient names, ID numbers, and the types of assistance provided. This research aims to develop an application for the Implementation of the Vigenere Cipher Algorithm for Social Assistance Data Security in Lawe Sempilang Village. This application is designed to enhance the security of social assistance data by encrypting the data so that it can only be accessed by authorized parties, thereby preventing data leaks or misuse of information. The research method used is the Research and Development (R&D) method. This research successfully implemented the Vigenere Cipher algorithm in the data management system for social assistance recipients in Lawe Sempilang Village. With the presence of encryption, sensitive information such as Name, NIK, Phone Number, Email, Address, Dependents, and Income remains secure throughout the application process until approval by the Admin Department. The developed system is capable of maintaining data confidentiality and enhancing security in the distribution of social assistance. The results also show that the Vigenere Cipher algorithm succeeded in carrying out the encryption and decryption process correctly, so that only authorized parties can access the information in its original form.